Analysis of Benzene Exposure Levels on Commuters Traveling within the Metropolitan Area of Costa Rica - Villalobos-Gonzalez, Wendy (2015)
This study reports the benzene exposure levels of commuters traveling within the metropolitan area of Costa Rica using personal cars, buses, and urban trains. 47 in-vehicle samples were collected in the 2014 wet season under three different driving conditions: rush hour traffic, normal traffic and weekends. Samples were collected in Tedlar bags and analyzed using 75 μm carboxenpolydimethylsiloxane (CAR/PDMS) and gas chromatography with flame ionization detection (GCFID). Additionally, duplicate samples were collected on adsorption tubes filled with Tenax TA and analyzed by thermal desorption (TD) and GC-FID. Results indicate that travelling in cars and buses under rush hour conditions exposes commuters to statistically equal average benzene concentration of 48.7 and 51.6 μg/m3, respectively. Average benzene levels in urban trains (33.0 μg/m3) were measured only during morning rush hours. Greater benzene levels in buses than personal cars concentrations may be attributable to the immersion of traffic-related emission within the bus cabins. Factors, such as the driving pattern, the number of vehicles on the route, the road infrastructure, and the prevalence of gasoline-fueled vehicles in Costa Rica, may increase ambient benzene concentrations. Benzene levels inside car cabins reported in this study are in the range of those reported in other urban areas; however, the corresponding concentrations inside buses and urban trains (rush hour only) are higher than previously published exposure levels.